Efektivitas Pemberian Bantuan Hukum Struktural dalam Proses Penyelesaian Perkara Pidana Secara Litigasi dan Non-Litigasi - Fajargus Laia; Susilawati Susilawati; Maria Rosalina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The purpose of this paper is to determine the legal arrangements for providing structural legal aid, what are the forms of litigation and non-litigation resolution, and how the obstacles are faced. The research is descriptive in nature, by describing the state of the subject and object, which can be people or institutions based on existing facts and uses a normative and empirical juridical approach, namely analyzing laws and regulations and conducting interviews with respondents. Data obtained through field research (field research). Based on the results of the research, the arrangements for providing structural legal aid by the Medan legal aid agency are Law No.16 of 2011 concerning legal aid and Government Regulation No. 42 of 2013 as the implementing regulation, and as for internal assistance, namely the standard operating procedures of the legal aid agency itself and other supporting laws. Field legal aid agencies resolve criminal cases in litigation and non-litigation terms. Litigation resolution is the handling of cases through court channels, namely acting as a companion, both in the police, prosecutors, and in court. Meanwhile, non-litigation settlement is the handling of cases outside the court route, namely by conducting legal counseling, legal consultation, mediation, and negotiations, which can be carried out by lawyers, paralegals, lecturers, and law faculty students who have met the requirements that have been set.